STUDY OF EDUCATIVE EPIC CHARACTERS IN THE FOLK STORY "PONDALOS" ACCORDING TO VLADIMIR PROPP AND ITS IMPLICATIONS FOR LEARNING INDONESIAN LANGUAGE - Felicia Worotikan; Santje Iroth; Fince Sambeka M.Hum (Journal of Learning on History and Social Sciences, 2024)
This research aims to examine the character of the educational epic in the folk tale "Pondalos" based on Vladimir Propp's structural theory and its implications for Indonesian language learning. The research method used is descriptive qualitative with document analysis and library research. The research results show that there are 25 functions contained in the folklore "Pondalos" according to Vladimir Propp's theory, including offense, surveillance, conveyance, fraud, involvement, crime, intermediary, and others. Meanwhile, the educational epic character in this story is found in the character Pondalos who shows courage, ingenuity and ability to face difficult challenges. The implication in learning Indonesian is that the folklore "Pondalos" can be used in learning Indonesian to understand the moral values and heroism in folklore. This research contributes to the preservation of cultural heritage and the development of Indonesian language learning.